Triple Teeth: Report of an Unusual Case - Prashant Babaji; M. A. Prasanth; Ajith R. Gowda; Soumya Ajith; Henston D'Souza; K. P. Ashok (Case Reports in Dentistry)
Fusion or synodontia is a union of two or more than two developing teeth. Commonly fusion occurs between teeth of the same dentition, mixed dentition, or between normal and supernumerary teeth. Fused primary teeth present with several clinical problems like caries, periodontal problem, arch asymmetry, delayed eruption, ectopic eruption of succedaneous teeth, aesthetic, and other complications. This paper presents a rare and unusual case of triple teeth in mandibular primary dentition.